Respuesta :
Answer:
X = 0 ; y = 10 ; 10 = a(0) + b(0) + c
c = 10\
x=2 ; y = 15 ; 15 = a(4) + b(2) + 10 ; 5 = 4a+2b
x=4 ; y=18 ; 18 = a(16) + b(4) + 10 ; 8 = 16a + 4b
2(5) = (4a+2b)2
-
8 = 16a + 4b
2 = -8a a = -0.25
b = 2 y = (1/4)x^2 + 2x + 10 ; 4y = x^2 + 8x + 40
Answer:
X = 0 ; y = 10 ; 10 = a(0) + b(0) + c
c = 10\
x=2 ; y = 15 ; 15 = a(4) + b(2) + 10 ; 5 = 4a+2b
x=4 ; y=18 ; 18 = a(16) + b(4) + 10 ; 8 = 16a + 4b
2(5) = (4a+2b)2
-
8 = 16a + 4b
2 = -8a a = -0.25
b = 2 y = (1/4)x^2 + 2x + 10 ; 4y = x^2 + 8x + 40
Step-by-step explanation:
x=2 ; y = 15 ; 15 = a(4) + b(2) + 10 ; 5 = 4a+2b
x=4 ; y=18 ; 18 = a(16) + b(4) + 10 ; 8 = 16a + 4b
2(5) = (4a+2b)2
-
8 = 16a + 4b
2 = -8a a = -0.25
b = 2 y = (1/4)x^2 + 2x + 10 ; 4y = x^2 + 8x + 40